Promotion and Communication Strategy of Educational Institutions at Man 4 Pandeglang - Iwan Setiawan; Abdul Mui`in; Anis Zohariah (MultiTech Publisher, 2023)
Education is one of the key aspects in sustainable community development. To achieve success in providing education, effective promotion and communication strategies are needed. MAN 4 Pandeglang, as a secondary education institution in Pandeglang, has its own challenges in improving the image and attractiveness of the school. Therefore, this research aims to explore the promotion and communication strategies that have been implemented at MAN 4 Pandeglang. This research method uses a qualitative approach with data collection techniques in the form of in-depth interviews, observation and document analysis. Research respondents included school management staff, teachers, students and parents. The research results show that MAN 4 Pandeglang has implemented various inclusive and diverse promotional and communication strategies. This strategy includes the use of social media, school exhibitions, educational seminars, and collaboration with related parties. Apart from that, MAN 4 Pandeglang has also created creative programs such as making school promotional videos and actively involving students in promotional activities. It can be concluded that the promotion and communication strategies that have been implemented at MAN 4 Pandeglang have had a positive impact in improving the image and attractiveness of the school. This research provides valuable insights for other schools facing similar challenges in improving student attendance and school reputation. In addition, this research also provides further understanding of how inclusive and diverse approaches in promotion and communication can influence public perceptions of educational institutions